2010
DOI: 10.1002/ajmg.a.33401
|View full text |Cite
|
Sign up to set email alerts
|

Subtelomeric deletion of 12p: Description of a third case and review

Abstract: Only 12 cases with a cytogenetically visible deletion of the short arm of chromosome 12 (12p) have been reported so far. The difference in clinical features observed in these patients indicates that there is no distinct phenotype associated with this short arm deletion, although the existence of a del(12p) syndrome was previously suggested. Besides those 12 reports, only two patients have been described with a subtelomeric 12p deletion; both present in the same family in which the son showed a mild phenotype o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Although, the severity of the anomalies seen in these cases does not appear to correlate with the size of the deletion, it has been suggested that the variation in the clinical features seen in patients with del(12p) may be explained by the different sizes and locations in 12p of the deleted segments [Kivlin et al, 1985]. It is tempting to speculate that another genetic aspect may be implicated, such as imprinting or copy number variation [MacDonald et al, 2010]. The function of NRXNs in synaptic activity make the neurexin genes strong candidates that contribute to ASD [Nussbaum et al, 2008].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Although, the severity of the anomalies seen in these cases does not appear to correlate with the size of the deletion, it has been suggested that the variation in the clinical features seen in patients with del(12p) may be explained by the different sizes and locations in 12p of the deleted segments [Kivlin et al, 1985]. It is tempting to speculate that another genetic aspect may be implicated, such as imprinting or copy number variation [MacDonald et al, 2010]. The function of NRXNs in synaptic activity make the neurexin genes strong candidates that contribute to ASD [Nussbaum et al, 2008].…”
Section: Discussionmentioning
confidence: 92%
“…In the literature, at least twelve patients with interstitial deletion on the region of 12p have been reported till date [Stumm et al, 2007;MacDonald et al, 2010]. These patients' clinical phenotype are summarized in Table I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 12p13.33 microdeletion is a rare condition that has only been described in four case reports (three subtelomeric and one interstitial). [25][26][27][28] It is associated with ID and various psychiatric manifestations ( Table 1). The age at which the first words are uttered was delayed in 2/4 patients, but no specific data regarding speech production troubles have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…These similarities fostered the suggestion of a syndrome: the 12p deletion syndrome. However, other cases presenting a variety of phenotypes were described, hence leading to the rejection of the existence of such a syndrome [MacDonald et al, 2010]. Thevenon et al [2013] studied 9 patients with 12p13.3 microdeletions, and although findings marked phenotypic variability between patients, most of them presented childhood apraxia, intellectual disability, and psychiatric manifestations.…”
mentioning
confidence: 99%